PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DI KELAS IV SEKOLAH DASAR - Ikhsan, Muhamad; Hamimah, Hamimah; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis research was motivated by the low learning outcomes in social studies learning. This is because the teacher has not applied the right and varied learning model so that students have not been able to solve the problems that arise. Therefore, action was taken using the Cooperative Teams Games Tournament (TGT) model. The purpose of this study is to improve learning outcomes of social studies using the Cooperative Teams Games Tournament (TGT) model.The type used of this study is classroom action research. This study activity consists of stages of learning implementation which includes two cycles consisting of planning stages, implementation, observation and reflection. Data obtained from the subject under study, namely teachers and students. The source of research data is the process of learning social studies using a cooperative model type Teams Games Tournament (TGT). The subject of the study was teachers and 25 students in fifth grade. consisting of 10 male students and 15 female students. The approach used is a qualitative and quantitative approach. The study data is in the form of information about the process and the results of action data obtained from the results of observations and tests.The study in the first cycle obtained an average observation of lesson plans percentage of 69.64% (B), the average observation results, teacher aspects 83.35% (B), the average observation results, aspects of students 83.35% (B ), and the average student learning outcomes are 72.7 (C). In the second cycle, the observation results of RPP 92.86% (SB) were obtained, the results of the observation of teacher aspects were 95.8% (SB), the results of observations were 95.8% (SB), and the average student learning outcomes 85.23 ( SB). Based on the results of the study concluded that social studies learning using the Cooperative Learning, Teams Games Tournament (TGT) model can improve student learning outcomes.   Keywords: Cooperative Model, Teams Games Tournament, Social Studies Learning